Mapping Online Geographical Indication: Agri-Food Markets on E-Retail Shelves - Guilherme Silva Fracarolli (Agronomy, 2021)
Economics has been trying to understand market functioning for a long time. However, the neoclassical approach does not satisfy the understanding of the mechanisms that operate in the construction, stabilization, and transformation of markets. For this reason, economic sociology proposes to provide subsidies from causal pluralism, rejecting explanatory theories of purely rational choices. Therefore, the use of sociological theories in the understanding of agri-food markets is also necessary. In this sense, this work aimed to compare the market for agri-food products with a geographical indication (GI) between the European Union (EU) and Mercosur, based on the performance of brands and supermarkets in both regions. For this, we used a data survey of thousands of products and respective GI registrations in the most prominent online markets of countries in both regions. We applied analyses that differentiated the economic blocs and used field theory to explain the phenomena found in the findings. The results indicated the formation of relevant bands in the GI market, a little voluminous, but capable of crossing borders, a second, with the majority of GIs found that are only commercialized locally, and a third invisible, where most products are located, which do not exist in these markets. Furthermore, supermarkets’ own brands have great relevance and are decisive in building the market.